Impact of harmonization of international standard nicsp3, "Accounting policies, changes in accounting estimates and errors" in the system integrated financial information SIIF- nation (2014)
The Standard IPSAS 3, "Accounting Policies, Changes in Accounting Estimates and Errors" provides two methods of application according to the time of application, retrospectively and prospectively, the first will be applied to correct the change in estimate or error, or failing policy change from previous periods bringing current date real balances, ie, as if political modified always been taken into account or estimates or errors never existed, the above taking into account the feasibility of establishing the impact of these on the financial statements of the ECP; prospective method indicates that changes or corrections were implemented from the current period with implications for future comparative method is applicable in case impossible to establish the impact on the financial statements retrospectively.